Prinsip-prinsip Etika Bisnis dalam Al-Qur'an Dan Hadits: Relevansinya Terhadap UMKM di Kota Bogor - Said Safri Ibrahim; Achmad Syamsul Huda (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study explores the relationship between the principles of business ethics in the Qur'an and Hadith and the practices of micro, small, and medium enterprises (MSMEs) in Bogor City. Employing a descriptive qualitative approach, data were collected through in-depth interviews and knowledge-based tests involving 15 MSME actors from various business sectors. Data analysis was conducted using NVivo software to identify the dominant themes emerging from the respondents' narratives. The findings reveal that ethical values such as honesty, trustworthiness (amanah), justice, transparency, and responsibility are widely understood and applied in their daily business operations. Among these, honesty emerged as the most dominant theme, reflecting a strong commitment to integrity in business practices. However, challenges in applying these ethical principles persist, including intense market competition, concerns about declining profits, and limited awareness among some business actors regarding the importance of Islamic ethics in commerce. This research underscores the significance of integrating Islamic ethical values into MSME practices to foster a more sustainable and just business ecosystem.